2017
DOI: 10.1002/joc.4978
|View full text |Cite
|
Sign up to set email alerts
|

Does summer precipitation trend over and around the Tibetan Plateau depend on elevation?

Abstract: The Tibetan Plateau (TP) experienced a rapid warming and wetting in recent decades. The elevation dependence of warming rate has been established, while the question of trend in precipitation against the elevation gradient remains open. By using the in situ observation of precipitation, air temperature, and surface specific humidity from 91 stations over and around the TP, this study investigated how the trends in summer precipitation varied along the elevation gradient over and around the TP during the period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 54 publications
3
41
0
2
Order By: Relevance
“…The majority of the stations in semi‐arid and humid‐zones of central TP shows increasing precipitation trends, while at the periphery, decreasing trends have been observed. Summer precipitation increased with elevation (1000–4500 m) over TP from 1970 to 2014 at a rate of 0.83% decade −1 km −1 (Li et al ., ). The moisture transports from the west by westerlies and from the southwest by the Indian summer monsoon likely contributed the most to the precipitation over the TP (Zhang et al ., ).…”
Section: Changes In the Climatic Indicators Over The Tpmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the stations in semi‐arid and humid‐zones of central TP shows increasing precipitation trends, while at the periphery, decreasing trends have been observed. Summer precipitation increased with elevation (1000–4500 m) over TP from 1970 to 2014 at a rate of 0.83% decade −1 km −1 (Li et al ., ). The moisture transports from the west by westerlies and from the southwest by the Indian summer monsoon likely contributed the most to the precipitation over the TP (Zhang et al ., ).…”
Section: Changes In the Climatic Indicators Over The Tpmentioning
confidence: 99%
“…This is greater than the rate in Northern Hemisphere (0.38 °C decade −1 ) and almost 1.5 times the rate of global warming (0.32 °C decade −1 ) (Zhang et al ., ). Recent studies (Liu et al ., ; Qin et al ., ; Pepin, ; Guo et al ., , ; Li et al ., ) have reported that the changing trends in air temperature, wind speed, and summer precipitation are elevation‐dependent in the TP and its surroundings. Because of its high sensitivity to climate change, TP changes are considered as an indicator of global warming effects (Yao et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…In recent years, EDW becomes an interesting area of research for understanding the climate change phenomenon. Related studies revealed that warming at higher altitudes is more obvious than that at lower altitudes (You et al, 2010;Guo et al, 2016a;Li et al, 2017;Sun et al, 2017;You et al, 2017). However, many studies have also stated that there are no clear evidence of EDW phenomenon (You et al, 2008).…”
Section: Elevation-dependent Warmingmentioning
confidence: 99%
“…In JJA and SON, precipitation increase is still the largest for QM_3km, followed by that for QM < 2 km, and is the least for QM_2km. The results imply that the precipitation wetting becomes more pronounced at higher elevations than at lower elevations in the QM from 1960 to 2014 as warmer air in mountain regions can hold more moisture according to the Clausius–Clapeyron relationship (Wentz et al, ; Trenberth, ; Li et al, ). The increasing trends for precipitation in DJF and MAM are more obvious at elevations of QM_2km than at other elevations, which show no strict elevation dependency of precipitation increasing trends.…”
Section: Resultsmentioning
confidence: 98%
“…Reanalysis data sets are the results of data assimilation making use of a background model forecast together with applicable observations, including their number and type (Wang and Zeng, ; You et al, ). These components, the model physical parameterizations, as well as satellite data processing are responsible for part of the uncertainties (Bosilovich et al, ; Ma et al, ; Li et al, ). Spurious variations in reanalysis data sets suffer from discontinuities in radiosonde observations, even for the modern satellite era from 1979 to present when satellite observations play an ever‐increasingly important role in restraining upper atmosphere (Zhao et al, ).…”
Section: Resultsmentioning
confidence: 99%